UI/UX Design of a Web-based Automated Essay Scoring System using the Double Diamond Method - Akhmam Fahmi; Talitha Nurshafiyyah Supardi; Misna Asqia (SISTEMASI, 2026)
Manual essay assessment is often time-consuming and increases educators' workload, creating the need for an automated essay scoring system that can improve the efficiency of the assessment process. To address this need, the Nurul Fikri Integrated Institute of Technology (STT-NF) has developed the Essay Analytic Online (ESAO) platform. However, discussions with the platform developers and administrators revealed several UI/UX issues, including an outdated interface design, unclear feature presentation, login-related usability problems, and inconsistencies in interface elements that negatively affect system usability. This study aims to design the UI/UX of the ESAO web platform using the Double Diamond Design Framework to produce a more intuitive, consistent, user-friendly interface that better meets user needs. The design process followed the four phases of the Double Diamond Framework—Discover, Define, Develop, and Deliver—resulting in user flows, a design system, and high-fidelity prototypes developed in Figma. The proposed design was evaluated using the Single Ease Question (SEQ) method involving 20 participants, comprising students and lecturers from STT-NF, across five task scenarios. The evaluation yielded an overall mean SEQ score of 6.46 on a 7-point scale, with average scores of 6.48 for students and 6.30 for lecturers. All task scenarios achieved scores above the usability acceptance threshold of 5.0, indicating a high level of perceived ease of use. These findings demonstrate that the proposed UI/UX design effectively enhances the usability of the ESAO platform. Nevertheless, the evaluation was limited to ESAO users within STT-NF. Future studies are therefore recommended to involve a more diverse group of participants to obtain more comprehensive and generalizable usability evaluation results.